Synthesis of Monosubstituted 1,1-Dicarbonyl Ester 1,3-Dienes - Rousseau, Olivier; Delaunay, Thierry; Robiette, Raphaël (Synlett, 2014)
The synthesis of various electron-deficient 1,1-dicarbonyl ester 1,3-dienes substituted in position 2 or 3 of the diene moiety has been developed.
Keywords: bromine; condensation; cross-coupling; 1,3-dienes; malonates